Study of spectral and luminescence properties and association in hydrocarbon solvents of stilbene and distyrylbenzene derivatieves - Shershukov, V.M.; Bedryk, A.I.; Doroshenko, A.O. (Functional Materials, 2007)
Spectral and luminescence properties and association of stilbene and distyrylbenzene derivatives in hydrocarbon solvents have been studied. The bulky triphenyl amine group being a strong electron donor introduced in those molecules has been shown to make it possible to obtain efficient yello-green organic luminophors not inclined to association.